FOLK MUSIC ART IN THE CONTEXT OF WORLD CLASSICS - Мельничук, Святослав; Мельничук, Максим (SWorldJournal, 2024)
The article examines the elements of folk music in classical musical compositions and their perception from the perspective of a new metamodern society. In our scientific research, we explain that the original classical music originates from one rather